Problems of the Organization of the Labor Process that Affect the Effectiveness of the Work of Kazakhstani Doctors - Gulden Aldabergenova; Assiya Turgambayeva; Luca G. Brusati (Tehran University of Medical Sciences, 2021)
No Abstract